ANALISIS KEKERASAN TERHADAP ANAK DALAM NOVEL THE GIRL NEXT DOOR KARYA JACK KETCHUM - Naray, Agly Andre; Wantasen, Isnawaty L.; Ranuntu, Garryn Ch. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTThis research entitled ?The Analysis of Children Violation in the Novel The Girl Next Door by Jack Ketchum is written to fulfill the requirement of accomplishing bachelor?s degree in English Department Faculty of Humanities, Sam Ratulangi University. The focus of this study is to identify and classify the types of violence against children reflected in this novel, and the impact experienced by the main character, Meg. The writer used the concept of Child Abuse by Tracy Natasha (2012) to analyze the types, the causes, and the impacts toward victim. The writer also used the theory of Literature by Wellek and Warren to identify the intrinsic approach such as the plot, theme, and character. The result of this research shows four types of violation suffered by the victim, such as emotional, physical, sexual, and neglect based on the plot, the dialogues between the characters, and the actions portrayed in the novel.       Keywords: Child Abuse, Neglect, Violation, Literature